Structural Performance of Prefabricated Composite Girders for Railway Bridges along with Girder-to-Deck Interface Connections for Mechanical Injection - Hung Thanh Diep; Jiho Moon; Byung H. Choi (Applied Sciences, 2023)
Recently, to resolve a growing need for durable and resilient railway bridge construction/reconstruction systems, a great amount of research has been carried out in many countries. As a part of such studies, prefabricated composite girders with an innovative girder-to-deck connection have been proposed that facilitate construction by eliminating interference during on-site processes. In this study, a railway bridge prototype of prefabricated composite girders with girder-to-deck connections was designed to facilitate future application enhancement of off-site construction. Then, prefabricated composite girders were developed by deploying different girder-to-deck connections through geometric detailing of reinforcement, headed stud connectors, and precast decks. Based on the calculation theory of interface shear transfer, the detailed design of different girder-to-deck connections was carried out, in particular the reinforcement spacing. Furthermore, finite element analysis of prefabricated composite girders was conducted to determine the flexural moment strength of prefabricated composite girders. Parametric studies were carried out to consider the factors affecting the detailed design of the connection, ensuring that the connection is correctly designed, thereby ensuring the structural performance of prefabricated composite girders. From the results, conclusions were drawn. The developed cases satisfied the interface shear criteria according to both conventional and plastic approaches. There was no significant difference in flexural moment strength between the developed cases since all cases were designed with the full shear connection. In all cases, the flexural performance was ensured and can be used for railway bridges. The most optimum case of prefabricated composite girders is selected in specific design situations.